Structural elucidation and molecular docking of novel compounds from Annonamuricata fruit reveal anticancer potential against PI3k (Funded Work) - KAMBLE SANDHYARANI; LAXMIKANT H KAMBLE (International Journal of Pharma and Bio Sciences, 2017)
Cancer is the major public health burden in both developed and developing countries. Several synthetic agents are used to cure the disease but they have theirtoxicity and hence the research is going on to investigate the plant derived chemotherapeutic agents which are safe. Traditionally, drugs were discovered by developing synthetic compounds which is a time consuming multi-step processes against a battery of in vivobiological screens and further investigating the promising candidates for their pharmacokinetic properties, metabolism and potential toxicity. Sophisticated Insilico approaches has given a tremendous opportunity to pharmaceutical companies to identify new potential drug targets which in turn affect the success and time of performing clinical trials for discovering new drug targets. The aim of this research is to explore the antioxidant and anticancer activities of Annonamuricata. In present study using TLC-bio -autography and insilico screening, structure based molecular dockingoffour compoundsderived from chloroform extract of fruit of Annonamuricata was performed. In the present study, software like Autodock 1.5.6, Marvin view and Discovery studio 4.1visualizer were used. The compounds under investigation were Phytosphingosine, Dihydroergocoronine, Cetylpyridinium, and Dihydrospingosine. These four compounds are obtained from HR-LCMS analysis and these fourcompounds were docked against the5itd, it which is the PDB ID for PI3Kprotein derived from cancer pathway. The binding energies of these compounds; viz. Phytosphingosine, Dihydroergocoronine, Cetylpyridium, and Dihydrospingosine are -4.82kcal/mol, -7.93kcal/mol, -5.24kcal/mol,-3.97 kcal/mol respectively. This,Insilico approach reveals phytochemicals from Annonamuricata extract shows the potential to be an anticancer agent.